ANALYSIS AND DESIGN OF DATA WAREHOUSE AND DATA MART BUDGET - Hendra Maryanto; Bambang Purnomosidi Dwi Putranto; Rikie Kartadie; Muhammad Guntara; Robertus Saptoto (LPPM UTDI (d.h STMIK AKAKOM) Yogyakarta, 2023)
University as higher education institutions must be able to manage budgets properly. The budget is a future financial plan which includes the expectations of university management. This research will design a data warehouse, which is a place where data can be stored on a large scale. In this research, a data warehouse will be designed as a place to store budget data. The method applied in this study is the Kimball method with a nine-step methodology. The result of this research is a data warehouse design and budget data mart